Developmental reading 1 - Villanueva, Aida S.; Delos Santos, Rogelio L. (Quezon City, Philippines : Lorimar Publishing Company Inc., 2008)
This book on Development reading 1 is aligned with the CHED prescribed new teacher education curriculum that is reflective of the National Competency-Based teacher Standards with the end view of contributing to the formation of the ideal professional teacher.
Foreword iii -- Preface and Acknowledgment iv -- A Preview on Reading 7 The History of Reading 10 -- Reading as a Physiological Process 13 -- Reading as a Cognitive Process 17 -- Reading as a Communication Process 20 -- Reading as Skill/Skills 23 -- Reading as a Psycho-Social Process 26 -- Reading as a Process of Development 28 -- Obstacles to Reading 32 -- Selective Reading 35 -- Reading Comprehension 38 -- A Basic Technique in Reading Comprehension 40 -- An Overview of Speed Reading 42 -- Theories on Teaching Reading 46 -- The Top-Down Approach 46 -- Bottom-Up Reading Model 48 -- Interactive Reading Model 50 -- Literary Appreciation Skills 51 -- Reading for Specific Purposes -- Reading for Information 66 -- Reading for Appreciation and Enjoyment 69 -- Reading for Critical Understanding 89 -- Reading for Study 91 -- Applied Reading Skills -- Vocabulary Skills 94 -- Comprehension Skills 123 -- Study Skills 135 -- Bibliography 152
Includes bibliographical references.
Keywords: READING